Correlation between retinal vein occlusion and cancer – a nationwide Danish cohort study. Issue 8 (2nd October 2018) - Toft‐Petersen, Anne Pernille; Muttuvelu, Danson V.; Heegaard, Steffen; Torp‐Pedersen, Christian
Abstract: Purpose: To explore the association between retinal vein occlusion (RVO) and incident cancer. Methods: All Danish citizens with a first‐time diagnosis of RVO and no previous diagnosis of cancer in the period from 1 January 2004 to 31 December 2014 were included. Five likewise cancer‐free, age‐ and gender‐matched controls were included in a control cohort. All were followed up for 5 years or until either first diagnosis of cancer or death. Proportional hazards models with adjustment for age, gender, year of diagnosis and covariates and death as competing risk were used to estimate the risk of being diagnosed with cancer. Results: There were 7963 RVO patients without cancer at the time of diagnosis, and all could be matched to likewise cancer‐free controls. Half of RVO patients were male, and the median age at RVO diagnosis was 70 years (61–79). The control cohort was similar in terms of gender and age. The risk of cancer within 1 year was 1.8 among RVO patients and 1.5 among controls. The crude risk of cancer was 1.22 (1.11;1.34) and upon full adjustment 1.15 (1.05;1.27). No time dependency was detected, and the types of cancer developed in RVO patients and controls were similar. Conclusion: Retinal vein occlusion (RVO) diagnosis is associated with an increased risk of being diagnosed with cancer. This risk is likely to reflect shared risk factors rather than a causal association.